Reviews of recent publications - various authors (Studies in 20th & 21st Century Literature, 1992)
Brown, Frieda S., Compitello, Malcolm Alan, etc., Editors. Rewriting the Good Fight Critical Essays on the Literature ofthe Spanish Civil War by John Crispin Connor, Steven. Samuel Beckett: Repetition, Theory and Text by Maria Minich Brewer Jordan, Barry. Writers and Politics in Franco's Spain by Salvador J. Fajardo Lindenberger, Herbert. The History in Literature: On Value, Genre, Institutions by Raylene O'Callaghan
Keywords: Frieda S. Brown; Malcolm Alan Compitello; Rewriting the Good Fight Critical Essays on the Literature of the Spanish Civil War; Steven Connor; Samuel Beckett: Repetition Theory and Text; Barry Jordan; Writers and Politics in Franco' s Spain; Herbert Lindenberger; The History in Literature: On Value Genre Institutions; John Crispin; Maria Minich Brewer; Salvador J. Fajardo; Raylene O' Callaghan